TEACHER’S CREATIVITY AND INNOVATION IN MAKING TEACHING MATERIALS IN PANDEMIC TIME - Putri Nur Rahmawati; Enung Hasanah (Jurnal Administrasi Pendidikan, 2021)
This study aims to explore how the process of innovation and creativity of teachers in private elementary schools in Cilacap in making teaching materials during the Covid-19 pandemic. The method used in this research is qualitative research methods. Participants in this study were one teacher who we determined using purposive sampling technique, with the criteria: private SD teachers in Cilacap City, developing  innovative materials, and we collected data through online interviews. The results showed that the teaching materials used by teachers in the learning process in private schools in urban areas; participants took several stages to make creative and innovative teaching materials during the Mas pandemic. The steps are as follows: (1) analyze the needs of teaching materials (2) compile a map of teaching materials (3) structure the teaching materials, and (4) synchronize with school’s curriculum. Distance learning is the best alternative for schools to do during the covid- 19 pandemic. To be able to produce effective distance learning, teachers must innovate and be creative to develop teaching materials that can be used as media for distance learning. Teachers at private elementary schools in Cilacap City are among those who have been able to develop innovative teaching materials during the Covid-19 period so that learning becomes useful.